2017
DOI: 10.1002/2016wr019353
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical analysis of non‐Gaussian heterogeneity effects on subsurface flow and transport

Abstract: Much of the stochastic groundwater literature is devoted to the analysis of flow and transport in Gaussian or multi‐Gaussian log hydraulic conductivity (or transmissivity) fields, Ytrue(boldxtrue)=ln⁡Ktrue(boldxtrue) (x being a position vector), characterized by one or (less frequently) a multiplicity of spatial correlation scales. Yet Y and many other variables and their (spatial or temporal) increments, ΔY, are known to be generally non‐Gaussian. One common manifestation of non‐Gaussianity is that whereas f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 59 publications
9
16
0
Order By: Relevance
“…The GSG model is comprehensive and unique in that it captures simultaneously observed scaling behaviors of (a) the probability density distribution and (b) (statistical) moments of a random function and its increments. It does so by incorporating the concept of a truncated fractal introduced into the literature by Di Federico and Neuman (1997) and Di Federico et al (1999) Neuman (1990Neuman ( , 1991Neuman ( , 1995 to help explain the widely observed dispersivity scale effect (for a recent discussion of this effect and its explanation see Neuman, 2017). Di Federico and Neuman (1997) and Di Federico et al (1999) , it can immediately be down and/or upscaled to any other choices of these scales.…”
Section: Scalable Statistical Momentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The GSG model is comprehensive and unique in that it captures simultaneously observed scaling behaviors of (a) the probability density distribution and (b) (statistical) moments of a random function and its increments. It does so by incorporating the concept of a truncated fractal introduced into the literature by Di Federico and Neuman (1997) and Di Federico et al (1999) Neuman (1990Neuman ( , 1991Neuman ( , 1995 to help explain the widely observed dispersivity scale effect (for a recent discussion of this effect and its explanation see Neuman, 2017). Di Federico and Neuman (1997) and Di Federico et al (1999) , it can immediately be down and/or upscaled to any other choices of these scales.…”
Section: Scalable Statistical Momentsmentioning
confidence: 99%
“…Potential applications, such as those concerning environmental risk assessment and management, are virtually endless. An early step in this direction was taken by Riva et al (2017) 1 2…”
Section: mentioning
confidence: 99%
“…These concepts have already been employed in preliminary analytical and numerical studies of flow and transport in porous media whose log-conductivity is characterized through a GSG model. Riva et al (2017) present lead-order analytical flow and transport solutions in unbounded GSG log-conductivity fields under mean-uniform flow. Libera et al (2017) rely on a numerical Monte Carlo framework to analyze the joint effects of a GSG heterogeneous log-conductivity field and a temporally variable pumping rate on solute breakthrough curves (BTCs) detected at a pumping well operating in a twodimensional domain.…”
Section: Introductionmentioning
confidence: 99%
“…Libera et al (2017) rely on a numerical Monte Carlo framework to analyze the joint effects of a GSG heterogeneous log-conductivity field and a temporally variable pumping rate on solute breakthrough curves (BTCs) detected at a pumping well operating in a twodimensional domain. Besides spatial dimensionality, three major limitations can be identified for the analytical study by Riva et al (2017): ( ) macrodispersion is the only transport metric analyzed, ( ) the joint impact of local dispersivity combined with the heterogeneous advection driven by is not evaluated, and ( ) output uncertainty due to finite size of the medium is not considered.…”
Section: Introductionmentioning
confidence: 99%
“…Moment differential equations of groundwater flow have been recently applied to field settings (Riva et al, 2009;Bianchi Janetti et al, 2010;Panzeri et al, 2015), to non-Gaussian fields (e.g., Hristopulos, 2006;Riva et al, 2017) and have been embedded in geostatistical inverse modeling approaches (Hernandez et al 2003), stochastic pumping test interpretation (Neuman et al, 2004(Neuman et al, , 2007, or reactive solute transport (e.g., Hu et al, 2004). Most recent developments have allowed embedding stochastic MEs of transient groundwater flow in data assimilation/integration and parameter estimation approaches, e.g., via ensemble Kalman filter (Li and Tchelepi, 2006;Panzeri et al, 2013Panzeri et al, , 2015.…”
Section: Introductionmentioning
confidence: 99%